ANALISIS PEMAHAMAN WAJIB PAJAK UMKM TERHADAP INSENTIF PERPAJAKAN DI MASA PANDEMI COVID TAHUN 2020 - Hanung Triatmoko; Sri Suranta; Juliati Juliati; Trisninik Ratih Wulandari; Renata Zoraifi; Saktiana Rizki Endiramurti; Meka Sabilla Salim (ITB AAS INDONESIA, 2022)
This study aims to analyze the understanding of taxpayers of Micro, Small and Medium Enterprises (MSMEs) in the Karisidenan Surakarta area of the taxes provided by the government during the pandemic. Taxes have a regular end function, which means that taxes have a function to regulate the order of people's lives. Covid has resulted in a lot of MSMEs caused by the pandemic that the implementation of Large-Scale Social Restrictions (PSBB) in most areas in Indonesia, causing a decrease in people's purchasing power, especially for MSMEs which are the pillars of the Indonesian economy and contribute to GDP and employment. As a result, the government is considering policies that can be taken to support the sustainability of MSMEs so that the economy can continue to survive during the covid pandemic. One of the policy steps implemented was to provide tax incentives during the COVID-19 pandemic, namely the issuance of Minister of Finance Regulation (PMK) Number 44 of 2020 which was later revoked and replaced with PMK No. 86 of 2020 and lastly changed to PMK No. 110 of 2020. However, data that there are still many MSME actors who have not utilized or conducted this tax exhibition, it is necessary to dig deeper into the understanding of MSME actors towards taxes during the 2020 covid Keywords : MSMEs, Covid Pandemic, Tax Incentives